Comparative study of lignin stabilizing mechanisms in soil aggregates at virgin mixed broadleaf-pine forest and secondary broadleaf forest at Changbai Mountain Nature Reserve, Northeast China. (October 2020) - Feng, Yue; Han, Shijie; Wei, Yingqi; Xiao, Jianzhang; Geng, Shicong; Gu, Yue; Zhang, Yue; Chen, Wei; Zhang, Junhui
Highlights: Lignin stabilization was achieved by aggregate protection in broadleaf-pine forest. Lignin accumulation was enhanced by plant residues input in broadleaf forest. High macroaggregate proportion did not support great SOC sequestration in broadleaf forest. Abstract: The variation of soil organic carbon (SOC) stability is independent of the amount of SOC in the soil. For predicting the conservation of soil carbon in different forest ecosystems, it is crucial to investigate the mechanisms of plant derived residues allocation and stabilization in soil aggregates in different forest ecosystems. The role of aggregate protection in SOC sequestration (using lignin as a biochemical indicator) requires understanding of the interaction of many factors. We studied aggregate proportion, SOC amount and lignin phenol contents in the soil fractions from 0–5, 5–10 and 10–20 cm layers in a virgin mixed broadleaf-Korean pine (BK) and secondary broadleaf Betula-Populus (BP) stands at Changbai Mountain Nature Reserve, Northeastern China. Macroaggregates had higher lignin contents compared to the bulk soil in both BK and BP. The SOC and lignin contents in bulk soil and aggregates obviously declined with soil deepening in the two stands. BK exhibited more protected lignin in aggregates compared to the same particles from BP. The results suggested that the aggregates have limited capability to sequestrate more carbon, which causes carbon loss in the soil particles with soil depth increment in the secondary broadleaf forest. Stable lignin sequestration was achieved via effective aggregate protection in BK, while lignin occlusion was mainly regulated by the importation of plant residues into the topsoil of BP.